2016
DOI: 10.1190/geo2015-0427.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the anisotropic dynamic and static elastic moduli of unconventional reservoir shales: Implication for geomechanical investigations

Abstract: We obtained the complete set of dynamic elastic stiffnesses for a suite of "shales" representative of unconventional reservoirs from simultaneously measured P-and S-wave speeds on single prisms specially machined from cores. Static linear compressibilities were concurrently obtained using strain gauges attached to the prism. Regardless of being from static or dynamic measurements, the pressure sensitivity varies strongly with the direction of measurement. Furthermore, the static and dynamic linear compressibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 104 publications
(113 reference statements)
1
27
0
Order By: Relevance
“…The derived effective stress coefficient for ultrasonic velocities (dynamic) in the same specimens [ Ma and Zoback , ] was found to differ from that by the static volumetric strain shown in this study. Recent studies on dynamic and static properties in the same shale specimens also confirmed the fundamental differences between the two physical quantities and their sensitivities to stresses [ Meléndez‐Martínez and Schmitt , ; Ong et al , ]. Although the transmitting waves through the rock also induce strain (by vibration), the amount of dynamic deformation is a few orders smaller than the strain produced by the static loading [cf.…”
Section: Discussionmentioning
confidence: 99%
“…The derived effective stress coefficient for ultrasonic velocities (dynamic) in the same specimens [ Ma and Zoback , ] was found to differ from that by the static volumetric strain shown in this study. Recent studies on dynamic and static properties in the same shale specimens also confirmed the fundamental differences between the two physical quantities and their sensitivities to stresses [ Meléndez‐Martínez and Schmitt , ; Ong et al , ]. Although the transmitting waves through the rock also induce strain (by vibration), the amount of dynamic deformation is a few orders smaller than the strain produced by the static loading [cf.…”
Section: Discussionmentioning
confidence: 99%
“…Both the stress field and the evolving fracture network geometry influence the anisotropy of the strength (e.g., Sarout & Guéguen, ) and the elasticity (e.g., Sviridov et al, ) of deforming shales. Higher lithostatic stresses tend to reduce porosity, which increases the uniaxial compressive strength (e.g., Donath, ) and compressional wave velocity (e.g., Dewhurst & Siggins, ; Melendez‐Martinez & Schmitt, ; Ong et al, ; Sarout & Guéguen, ; Zadeh et al, ). Consequently, elastic wave velocity measurements have been used to infer the geometries of evolving porosity and fracture networks in shales (e.g., Baird et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Cheadle, Brown, and Lawton ; Homand et al . ; Melendez Martinez and Schmitt ). With regard to multi‐faced polyhedral, the measurements of Nara et al .…”
Section: Introductionmentioning
confidence: 99%
“…Examination of equation in light of the symmetry of S together with the requirement that there be at most five independent moduli demands ν 21 = ν 12 , ν 13 /ν 31 = E 1 /E 3 , and μ 13 = μ 31 . Melendez Martinez and Schmitt () review a number of the relationships between equations , , and useful for converting between stiffnesses, compliances, and engineering moduli; we include these in Appendix A for the sake of completeness.…”
Section: Introductionmentioning
confidence: 99%